2006
DOI: 10.1021/jm050907d
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y (NPY) Y4Receptor Selective Agonists Based on NPY(32−36):  Development of an Anorectic Y4Receptor Selective Agonist with Picomolar Affinity

Abstract: We have previously shown [Cys-Trp-Arg-Nva-Arg-Tyr-NH(2)](2), 1, to be a moderately selective neuropeptide Y (NPY) Y(4) receptor agonist. Toward improving the selectivity and potency for Y(4) receptors, we studied the effects of dimerizing H-Trp-Arg-Nva-Arg-Tyr-NH(2) using various diamino-dicarboxylic acids containing either di-, tri-, or tetramethylene spacers. These parallel dimers, 2A, 2B, 3, 4A, and 4B, and the corresponding linear tandem dimer and trimer analogues, 5 and 6, had enhanced selectivity and aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 38 publications
1
93
1
1
Order By: Relevance
“…Importantly, our 30-min time point used throughout these studies is earlier than time points at which physiological responses to PP have been observed. For instance, PP has been shown to significantly reduce food intake when measured at 1 or 2 and 4 (Balasubramaniam et al, 2006) h after i.p. administration.…”
Section: Immunohistochemistry For Determination Of Pp-induced Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, our 30-min time point used throughout these studies is earlier than time points at which physiological responses to PP have been observed. For instance, PP has been shown to significantly reduce food intake when measured at 1 or 2 and 4 (Balasubramaniam et al, 2006) h after i.p. administration.…”
Section: Immunohistochemistry For Determination Of Pp-induced Changesmentioning
confidence: 99%
“…We have previously shown that PP dose-dependently reduces food intake in freely fed and fasted mice and this effect was mediated through the Y4 receptor as it was completely abolished in Y4 receptor knockout mice (Balasubramaniam et al, 2006). To determine whether the LHA and/or the VMH may be involved in PP's effects on food intake and to map the neuronal pathways concerned, we investigated the expression of the early neuronal marker c-Fos in response to peripherally-injected PP.…”
Section: Pp Activates Neurons In the Lha And Vmhmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that PP decreases food intake with a delay of gastric emptying after peripheral administration in humans and rodents [105][106][107]. PP can interact with all subtypes of the Y receptor family, while it has the highest affinity toward Y4 receptors, particularly in the VMN, PVN, AP, and ARC [107][108][109].…”
Section: Pancreatic Polypeptide and Amylinmentioning
confidence: 99%
“…18,19 By contrast, the neurons in the lateral ARC coexpress proopiomelanocortin (also known as corticotropin-lipotropin) and cocaine-and amphetamineregulated transcript, which both promote weight loss by decreasing appetite. 20,21 Both the ARC and the brainstem are ideally positioned to interact with circulating humoral factors and to receive signals from the periphery. 22,23 Thus, gut hormones may function directly in the brain after being released into the circulation and signaling through circumventricular organs.…”
Section: Introductionmentioning
confidence: 99%